Miting v podderzhku Borisa El'tsina . Miting v podderzhku Borisa El'tsina . Rally in Support of Boris Yeltsin . Митинг в поддержку Бориса Ельцина - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Speech of Boris Yeltsin at the Rally, expressing the gratitude to Muscovites for support. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation) Выступление Бориса Ельцина на митинге с благодарностью москвичам за поддержку. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации)